2004
DOI: 10.1029/2004gl019535
|View full text |Cite
|
Sign up to set email alerts
|

Height‐integrated Joule and auroral particle heating in the night side high latitude thermosphere

Abstract: [1] Energy deposited at high latitudes by Joule and auroral particle heating perturbs the chemistry and dynamics of the neutral thermosphere. Height-integrated heating rates can be calculated by combining Super Dual Auroral Radar Network (SuperDARN) measurements with TIMED spacecraft Global Ultraviolet Imager (GUVI) auroral images. Spatial maps of heating rates are examined during two TIMED orbits and statistical averages are presented for quiet to moderate levels of geomagnetic activity. Joule heating dominat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
31
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 14 publications
(22 reference statements)
5
31
0
Order By: Relevance
“…Furthermore, within discrete aurora arcs the electric conductance has been reported to be anticorrelated with the electric fields [ de la Beaujardière and Vondrak , 1982; Marklund , 1984; Mallinckrodt and Carlson , 1985]. The Joule heating estimation from the simultaneous observations of the electric field and conductance from SuperDARN and the GUVI UVI have also suggested the effect of anticorrelating electric field and conductance [ Baker et al , 2004]. On the other hand, the Joule heating estimated from simultaneous observations of the Low Altitude Plasma Instrument electron flux and the IDM/RPA plasma drifts was affected very little by the positive/negative correlation of the electric field and conductance on average (Barbara A. Emery private communication, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, within discrete aurora arcs the electric conductance has been reported to be anticorrelated with the electric fields [ de la Beaujardière and Vondrak , 1982; Marklund , 1984; Mallinckrodt and Carlson , 1985]. The Joule heating estimation from the simultaneous observations of the electric field and conductance from SuperDARN and the GUVI UVI have also suggested the effect of anticorrelating electric field and conductance [ Baker et al , 2004]. On the other hand, the Joule heating estimated from simultaneous observations of the Low Altitude Plasma Instrument electron flux and the IDM/RPA plasma drifts was affected very little by the positive/negative correlation of the electric field and conductance on average (Barbara A. Emery private communication, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…If this Poynting flux is mapped onto the ionosphere, it reaches ∼100 mW/m 2 . This amount is sufficient to illuminate auroral emissions since the precipitating electron flux required for discrete auroral emissions is several tens of mW/m 2 at the ionospheric altitude [ Stenbaek‐Nielsen et al , 1998; Baker et al , 2004].…”
Section: Introductionmentioning
confidence: 99%
“…Their results are in good agreement with those of Foster et al [1983] and Ahn et al [1983] but larger than Palmroth et al [2004] simulation values. Baker et al [2004] found that Joule heating dominates in the evening sector auroral oval and also in the vicinity of the region‐1 current based on SuperDARN measurements and TIMED spacecraft Global Ultraviolet Imager (GUVI) auroral images.…”
Section: Introductionmentioning
confidence: 99%